NAD-dependent methylenetetrahydrofolate dehydrogenase-methenyltetrahydrofolate cyclohydrolase is targeted to the cytoplasm in insect cell lines. - Tremblay, G.B.; Sohi, S.S.; Retnakaran, A.; Mackenzie, R.E. (FEBS Letters, 1995)
Cytosolic NADP-dependent methylenetetrahydrofolate dehydrogenase-cyclohydrolase synthetase and the mitochondrial NAD-dependent methylenetetrahydrofolate dehydrogenase-cyclohydrolase (NMDMC) are differentially expressed during insect development although both enzymes are detectable at all stages. In contrast, cell lines derived from a variety of insect species express high levels of NMDMC but undetectable levels of the NADP-dependent enzyme. Northern analysis indicates the NMDMC message is expressed at levels 50-100 times higher in a Drosophila cell line compared to adult flies. RNase protection showed the predominance of shortened transcripts that require initiation at a downstream AUG producing a truncated protein that lacks a mitochondrial targeting sequence. These changes in expression effectively exchange the cytosolic NADP-dependent dehydrogenase for one with NAD specificity.